Upregulation of SLC2A3 gene and prognosis in colorectal carcinoma: analysis of TCGA data - Kim, Eunyoung (BMC Cancer, 2019)
BACKGROUND: Upregulation of SLC2A genes that encode glucose transporter (GLUT) protein is associated with poor prognosis in many cancers. In colorectal cancer, studies reporting the association between overexpression of GLUT and poor clinical outcomes were flawed by small sample sizes or subjective interpretation of immunohistochemical staining. Here, we analyzed mRNA expressions in all 14 SLC2A genes and evaluated the association with prognosis in colorectal cancer using data from the Cancer Genome Atlas (TCGA) database. METHODS: In the present study, we analyzed the expression of SLC2A genes in colorectal cancer and their association with prognosis using data obtained from the TCGA for the discovery sample, and a dataset from the Gene Expression Omnibus for the validation sample. RESULTS: SLC2A3 was significantly associated with overall survival (OS) and disease-free survival (DFS) in both the discovery sample (345 patients) and validation sample (501 patients). High SLC2A3 expression resulted in shorter OS and DFS. In multivariate analyses, high SLC2A3 levels predicted unfavorable OS (adjusted HR 1.95, 95% CI 1.22–3.11; P = 0.005) and were associated with poor DFS (adjusted HR 1.85, 95% CI 1.10–3.12; P = 0.02). Similar results were found in the discovery set. CONCLUSION: Upregulation of the SLC2A3 genes is associated with decreased OS and DFS in colorectal cancer patients. Therefore, assessment of SLC2A3 gene expression may useful for predicting prognosis in these patients. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12885-019-5475-x) contains supplementary material, which is available to authorized users.